Molecular determinants of transport function in zebrafish Slc34a Na-phosphate transporters - Werner, A; Patti, M; Zinad, HS; Fearn, A; Laude, A; Forster, I (American Physiological Society, 2016)
The epithelial Na+-coupled phosphate cotransporter family Slc34a (NaPi-II) is well conserved in vertebrates and plays an essential role in maintaining whole body levels of inorganic phosphate (Pi). A three-dimensional model of the transport protein has recently been proposed with defined substrate coordination sites. Zebrafish express two NaPi-II isoforms with high sequence identity but a 10-fold different apparent Km for Pi (KPi0.5). We took advantage of the two zebrafish isoforms to investigate the contribution of specific amino acids to Pi coordination and transport. Mutations were introduced to gradually transform the low-affinity isoform into a high-affinity transporter. The constructs were expressed in Xenopus laevis oocytes and functionally characterized. Becaue the cotransport of Pi and Na involves multiple steps that could all influence KPi0.5, we performed a detailed functional analysis to characterize the impact of the mutations on particular steps of the transport cycle. We used varying concentrations of the substrates Pi and its slightly larger analog, arsenate, as well as the cosubstrate, Na+. Moreover, electrogenic kinetics were performed to assess intramolecular movements of the transporter. All of the mutations were found to affect multiple transport steps, which suggested that the altered amino acids induced subtle structural changes rather than coordinating Pi directly. The likely positions of the critical residues were mapped to the model of human Slc34a, and their localization in relation to the proposed substrate binding pockets concurs well with the observed functional data.